Work Function Algorithm with a Moving Window for Solving the On-line k-server Problem - Baumgartner, Alfonzo; Manger, Robert; Hocenski, eljko (Journal of computing and information technology, 2007)
We consider a modification of the well known work function algorithm (WFA) for solving the on-line kserver problem. Our modified WFA is based on a moving window, i. e. on the approximate work function that takes into account only a fixed number of most recent on-line requests. The main motivation for using a moving window is to gain control over the prohibitive computational complexity imposed by the original algorithm. Experimental results are presented, where the performance of the modified WFA has been compared vs. the original WFA.